Revealing the Meaning of Mosque “Cash Balance”: A Phenomenological Approach - Mardian, Sepky; Nur, Mawardi; Ahnaf, Ahnaf (Universitas Ahmad Dahlan, 2024)
This study aims to reveal and comprehend the metaphorical meaning of the cash balance for mosque. This research conducted using a phenomenological approach that explores information as it is from managers through interviews, interactions, and researcher observations as well as visual documentation. Data processing, analysis, and discussion are carried out by researchers using a worksheet for the phenomenological analysis stage. The findings are discussed by critically confirming the related accounting concepts and previous research findings. The metaphorical meaning of the cash balance that can be extracted from the source is the cash balance as a trust, as programs evidence and as a beneficial evidence. This metaphorical meaning demands that managers manage mosque funds with the spirit of providing prosperity to society and the community, with faith in Allah and by inviting congregants to contribute to each other. In a broader sense, this metaphorical meaning indicates the embodiment of the manager's role and the functioning of the mosque beyond just a place of worship. The mosque has been made to function as a center for increasing the capacity of society through study and obtaining a sanad as well as a center for empowering benefits. This study contributes to find other meanings of cash balances outside the materialistic perspective that requires high cash balances as one of the mosque management performance indicators.